Multimedia demystified - Dowling, Jennifer Coleman (New York : McGraw-Hill, 2012)
"This practical guide provides a background on multimedia, and then delves into the elements that make up a successful multimedia project. You'll learn about software and hardware tools, digital photography, sound editing, web authoring with HTML, vector graphics, file formats, computer animation, and much more. Detailed examples and concise explanations make it easy to understand the material, and end-of-chapter quizzes and a final exam help reinforce key concepts"--
Machine generated contents note: PART ONE: Multimedia Overview: What It's All About -- I. Introduction to Multimedia -- A. What is Multimedia? -- B. A Concise History of Multimedia -- 1. Early Multimedia Computing -- 2. Hypermedia and Hypertext -- C. Combining Content from Various Media -- D. Linear vs. Interactive Multimedia -- 1. Linear Multimedia -- 2. Nonlinear Interactive Multimedia -- 3. Kinds of Multimedia -- E. Let's Get Technical -- F. Analog-to-Digital Evolution -- II. The Purpose and Application of Multimedia -- A. Benefits of Interactive Presentations -- 1. Avoiding Potential Pitfalls -- B. Uses of Multimedia -- C. Planning Stages and Development Process -- 1. Roles and Responsibilities of the Multimedia Team2. Information Architecture -- 3. Copyright Issues: Securing Permission for Media UsageD. Tools Required for Creating and Preparing Media E. Making it Functional and Interactive F. Finalizing, Testing, and Delivering Multimedia -- PART TWO: Kinds Of Media: The Essential Components -- III. Graphics and Images -- A. Designing Vector Graphics -- B. Creating Raster Images -- 1. Pixel-Based Displays -- 2. Working with Raster Graphics -- C. Scanning and Resolution -- D. Digital Photography -- E. Clip Art and Stock Images -- F. File Formats for Screen Display -- G. Color Theory: Pigment vs. Pixels -- 1. CMYK and the Subtractive Color Model -- 2. RGB and the Additive Color Model -- 3. Color for Digital Displays -- IV. Text and Typography -- A. Text Defined -- 1. Typing, Texting, and Emailing -- B. Words and Copywriting: How to Write Effective Content -- C. Typography -- 1. Fonts and Styles -- a. Serif vs. Sans Serif -- 2. Typographic Treatment: Designing with Type -- 3. Placement and Arrangement of Type -- D. Preparing Text for the Screen: Amount and Legibility/Readability -- 1. Type Sizes and Styles for the Screen -- 2. Screen vs. Print -- 3. Type on the Web -- V. Animation -- A. Animation in Multimedia -- 1. Functions of Moving Images -- 2. Advantages and Disadvantages of Animation -- 3. Interactive Animation -- 4. Kinds of Animation: Categorizing and Evaluating -- B. Traditional Animation Overview -- 1. Principles of Animation -- C. Concept Development and Storyboarding -- D. Differences Between 2D and 3D Animation -- 1. 2D Computer Animation: Frame-By-Frame and Tweening -- 2. 3D Animation: Modeling, Ray Tracing, and Rendering -- E. Animation Files and Formats -- VI. Audio: Music and Sound Effects -- A. Audio Fundamentals -- 1. Mechanics of Sound -- 2. Analog and Digital Audio -- B. Recording vs. Importing Audio -- 1. Amplitude, Frequency, and Sampling Rates -- C. MIDI and Digital Music -- D. Editing and Manipulating Audio Tracks -- E. Audio File Formats and Compression Schemes -- 1. Audio File Types -- 2. Storage Options -- F. Using Sound in Multimedia Projects -- 1. Web Site Audio -- 2. Mobile Device Audio -- VII. Video: Recording and Manipulating Moving Images -- A. Video Mechanics -- B. Video in Multimedia -- C. Analog and Digital Video -- 1. Composite vs. Component Signals -- 2. Analog-to-Digital Conversion -- 3. Video Resolution -- D. Shooting or Obtaining Video -- 1. Recording Raw Footage -- 2. Capturing Directly from TV -- 3. Importing Video to Computer -- 4. Acquiring Video Clips -- E. Display Standards and Playback Options -- F. Editing and Manipulating Video -- G. Video File Formats and Compression Schemes -- 1. Video File Types -- 2. Storage and Memory -- H. Using Video in Multimedia Projects -- VIII.Authoring for Multimedia Functionality -- A. Programming and Scripting to Create Interactive Environments -- B. Tools for Authoring -- 1. Tool Selection Considerations -- 2. Bandwidth for Web Projects -- C. Web Authoring with HTML -- 1. HTML Tags -- 2. JavaScript Programming -- 3. Web Page Formatting with CSS -- 4. Web Standards and Guidelines -- D. Interactive Design -- 1. Graphical User Interfaces -- 2. Screen Layout and Arrangement of Elements -- PART THREE: Tools For Creating Multimedia Projects: Hardware and Software Needed To Make It Happen -- IX. Hardware and Equipment Options -- A. Multimedia Project Equipment Setup -- B. Input Devices -- 1. Mice, Digitizing Tablets, and Trackpads -- 2. Keyboards -- 3. Scanners -- 4. Image and Motion Capture -- 5. Microphones -- 6. Touchscreens and Fingerprinting Technology -- 7. Digital Audio Recorders -- C. Output: Displays and Screens -- 1. Dual Monitors -- 2. Speakers and Headphones -- D. Data Storage -- 1. Internal Drives -- 2. External USB Drives and Large Capacity Hard Disks -- 3. Online and Networked Storage -- E. Computing Platforms -- 1. Desktop Computers -- 2. Mobile Devices and Operating Systems -- X. Software for Multimedia -- A. Multimedia Software Options -- B. Vector Graphics: Illustration and Line Art -- C. Digital Imaging: Photography and Bitmapped Images -- 1. Screen Captures and Recordings -- D. Page Layout and Typography -- E. Animation and Motion Graphics -- F. Audio and Video Recording and Editing -- G. Authoring and Web Design -- H. Presentations -- I. Media Players -- PART FOUR: Multimedia End Products: Putting It All Together -- XI. Multimedia Projects -- A. Categorizing Multimedia Uses -- B. Presentations -- C. Video and Animation -- D. Educational and Training Programs -- E. Web Sites -- F. Apps and Mini Software Programs -- G. Video Games -- H. Noteworthy Gadgets and Devices -- XII. Delivery Systems -- A. Multimedia Product Maintenance -- B. Troubleshooting and User-testing -- C. Disk vs. Web Preparation -- D. Presentation Options -- 1. Portable or Permanent Displays -- 2. Kiosks -- 3. Projection -- 4. Multiple Screens -- 5. Interactive Whiteboards -- 6. Touch Screen TVs and Handheld Devices -- 7. E-Readers -- 8. Video Game Consoles -- E. Delivering Multimedia -- Final Exam -- Web Resources -- Index.
Includes index.
Keywords: Multimedia systems; Computers / Interactive & Multimedia